OFR-95-83 Personal Dust Monitor - Light Scattering - Pedro Lilienfeld (The National Institute for Occupational Safety and Health (NIOSH), 1982)
The objective of this program was the development, design, and fabrication of six personal-sized completely self-contained dust monitors capable of real-time as well as time-averaged monitoring of the concentration of respirable particles in coal mines, in the range of 0.1 to 100 mg/m3. The operation of these monitors is based on light scattering and passive air sampling. The design stressed overall miniaturization, ruggedness, simplicity and versatility. These instruments incorporate a single-chip CMOS microprocessor to perform all signal processing, data display and storage, and timing functions. The overall dimensions of these devices are, approximately, 10 by 10 by 5 cm.